Carbamazepine-Induced Acute Pancreatitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
A 5-year-old mentally retarded child who developed pancreatitis during accidental acute carbamazepine (CBZ) intoxication is reported from the Department of Pediatrics, Ohio State University, Columbus, Ohio.